Differential Effects of PDE4 Inhibitors on Cortical Neurons and T-Lymphocytes - Ryo Hirose; Haruhiko Manabe; Koji Yanagawa; Etsuo Ohshima; Michio Ichimura (Elsevier, 2008)
Inhibitors of PDE4 (cAMP-specific phosphodiesterase) induce side effects, including nausea and emesis, that limit their therapeutic potential. We investigated the function of two catalytically active conformations of PDE4 (a low-affinity conformer detected by conventional cAMP hydrolytic activity and a high-affinity conformer detected by [3H]rolipram binding) in neuronal cells. We assessed enhancement of β-adrenoceptor-mediated cAMP accumulation in cortical neurons in vitro by eleven PDE4 inhibitors with diverse biochemical profiles. The compounds tested have a wide inhibition range of PDE4 catalytic activity and [3H]rolipram binding. Inhibition potency for PDE4 catalytic activity and [3H]rolipram binding for each compound was different. Potency in augmentation of cAMP correlated significantly with the inhibitory effect on [3H]rolipram binding, but not with that against PDE4 catalytic activity. On the other hand, the inhibitory effect on proliferation of T-lymphocytes of the same PDE4 inhibitors correlated both with inhibition of PDE4 catalytic activity and with inhibition of [3H]rolipram binding. These findings indicate that the high affinity PDE4 conformer exists at a high level in cortical neurons and is important in the regulation of cAMP. Furthermore, the relative contributions of the two PDE4 conformers in cell function may cause different PDE4 inhibitor effects on cortical neurons and T-lymphocytes. Keywords:: PDE4 inhibitor, rolipram, high-affinity rolipram binding site, neuron, T-lymphocyte